“PREVALENCE OF DIABETIC MACULAR EDEMA IN DIABETIC PATIENTS WHO UNDERWENT CATARACT SURGERY AS DETERMINED BY OPTICAL COHERENCE TOMOGRAPHY.” - Dr. D. Satyavardhana Rao; Dr. D. Preethi; Dr. Praveen Kumar Kv (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: The purpose of this study is to evaluate the prevalence of diabetic macular edema in diabetic patients who underwent cataract surgery and to analyze the postoperative development of diabetic macular edema in these eyes. Methodology: This is an interventional cross-sectional study. This study includes 75 patients with diabetes mellitus who underwent cataract surgery and without OCT changes in retinal thickness and morphology and, underwent a complete ophthalmic evaluation, fundus examination, and optical coherence tomography to detect the presence of diabetic macular edema. These examinations were executed baseline (preoperative), 7-10 days postoperative, one, three, and six months postop. Results: The present study, consisting of 75 individuals, shows that the largest portion of the sample falls within the 66-70 age group accounting for 21.3%, the sample ranges from 35-70 years old with an average mean age of 54.37, gender distribution shows a slightly higher presentation of males at 54.7% than females 45.3%. The present study indicates the prevalence of Diabetic Macular Edema (DME) in diabetics is 13.3% (10) Conclusion: According to the results of this study, diabetic macular edema (DME) is quite common among diabetic individuals who underwent cataract surgery. This was determined by objective assessments utilizing optical coherence tomography. Incorporating OCT into the routine care protocol for diabetic patients undergoing cataract surgery may enhance visual outcomes and diminish the likelihood of post-surgical complications such as diabetic macular edema.